Synthesis of a multicomponent cellulose-based adsorbent for tetracycline removal from aquaculture water - Tran, Uyen Bao; Vo-Tran, Ngoc Thanh; Truong, Khai The; Nguyen, Dat Anh; Tran, Quang Nhat; Nguyen, Huu-Quang; Lee, Jaebeom; Truong-Lam, Hai Son (Beilstein Journal of Nanotechnology, 2025)
Excessive use of tetracycline (TC) antibiotics in aquaculture, particularly in Vietnam, has contributed to environmental contamination and economic losses. To address this problem, we developed a novel cellulose-based multicomponent adsorbent material (PGC) synthesized from sodium carboxymethyl cellulose and investigated factors influencing its TC adsorption capacity. The synthesis process was optimized using parameters derived from the response surface methodology. The surface and structural properties of PGC were characterized, and the TC adsorption efficiency of PGC was assessed using high-performance liquid chromatography–mass spectroscopy (HPLC-MS). Elemental analysis of PGC identified four key mechanisms governing its endothermic TC adsorption mechanism: surface complexation, electrostatic interactions, hydrogen bonding, and CH–π interactions, with surface complexation between Ca2+ and TCs being dominant. Batch adsorption experiments conducted to examine the factors influencing adsorption capacity revealed that PGC achieved up to 70% TC removal efficiency at an adsorbent dosage of 40 mg and an initial TC concentration of 60 mg·L–1 at pH 6–7, reaching equilibrium after 12 h. The surface characteristics and structural properties of PGC were determined using various material characterization techniques, including FTIR, SEM, EDX, and BET. Verification experiments under optimal conditions confirmed that the adsorption process followed second-order kinetics and the Langmuir adsorption isotherm model. Under optimal experimental conditions, a maximum adsorption capacity (qm) of 123.2 mg·g−1 was estimated using the Langmuir isotherm model. These findings indicate that PGC demonstrates strong potential as an effective adsorbent for the removal of average 70% TC antibiotic residues, particularly oxytetracycline, chlortetracycline, TC, and doxycycline.
Keywords: adsorption; aquaculture water; removal efficiency; response surface methodology; tetracycline antibiotic